Implementation Of Bengkulu Utaran Regent Regulation Number 47 Of 2018 Regarding Policies And Strategy Of Bengkulu Utara Regency In Management Of Household Waste And Household Like Waste - Muhammad Nur Alfikri; Harmiati Harmiati; Edi Darmawi (Journal of Social Science and Humanities, 2023)
This study aims to describe the implementation of North Bengkulu Regent Regulation Number 47 of 2018 concerning North Bengkulu District Policies and Strategies in the Management of Household Waste and Household Waste-like Waste, in terms of the supporting factors for successful implementation, namely: communication, resources, disposition/attitude executive and bureaucratic structure. This type of research is qualitative research. The location of this research was at the North Bengkulu Regency Environmental Service. Informal selection technique is the informant of this research is snowball sampling. Data collection was carried out through author observation, in-depth interviews and documentation studies. Data analysis was carried out through descriptive data analysis techniques. The results of this study indicate that the implementation of waste management policies in North Bengkulu Regency based on North Bengkulu Regent Regulation Number 47 of 2018 has been going well, especially in Arga Makmur City, as the capital of North Bengkulu Regency and also as the center of government administration and the regional economy. However, for the whole area of North Bengkulu Regency it has not been implemented properly, due to geographical constraints, limited resources and facilities. The success of this implementation is supported by communication factors, resources, dispositions or attitudes of the implementers as well as a well-run bureaucratic structure and community participation. Several obstacles to the implementation of this regulation, in the form of socialization to the community which is still lacking and resource constraints to reach all areas of North Bengkulu Regency.